CFD experiments on a low crested sloping top caisson breakwater. Part 1. nature of loadings and global stability. (15th June 2019) - Buccino, Mariano; Daliri, Mohammad; Dentale, Fabio; Di Leo, Angela; Calabrese, Mario
Abstract: Random wave CFD experiments have been carried out to study the loading process on a sloping top caisson breakwater subject to significant overtopping. Numerical results suggest that since wave force under crest is reduced by the overpassing, wave pressures under trough become comparatively larger, leading the structure to fail seaward even in absence of violent impact events; this finding is consistent with what observed by Oumeraci (1994) in reviewing the failures of a number of vertical face breakwaters during the first half of 20th century. Present findings also show that wave pressures under trough may be significantly underestimated by the design formulae currently available. To face this issue, a set of simple alternative equations are proposed, based on the maximum momentum flux concept, originally introduced by Hughes (2004). A second part of the research work is dedicated to the occurrence of intense impulsive loadings at rear of the breakwater, caused by the huge inertia of the overtopping jet. The analysis of this interesting phenomenon is though presented in a separate paper.